2016
DOI: 10.1002/2015rs005906
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study for reconstructing the spatial‐temporal structure of TIDs from high‐resolution backscatter ionograms

Abstract: Over‐the‐horizon radar (OTHR) utilizes the reflective “sky wave” property of the ionosphere for high‐frequency radiowaves to illuminate targets at ranges extending to several thousand kilometers. However, the ionospheric “mirror” is not static but exhibits geographic, diurnal, seasonal, and solar cycle variations. NorthWest Research Associates has developed an ionospheric data assimilation capability called Global Positioning Satellite Ionospheric Inversion (GPSII; pronounced “gypsy”) that allows real‐time mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…At 400 km the perturbation marginally exceeds the background levels. These results are in agreement with earlier studies reporting that TID amplitudes maximize near or below the background electron density maximum hmF2 (e.g., Morgan & Ballard, 1978).…”
Section: Large Scale Tid Detection Methodologiessupporting
confidence: 94%
See 1 more Smart Citation
“…At 400 km the perturbation marginally exceeds the background levels. These results are in agreement with earlier studies reporting that TID amplitudes maximize near or below the background electron density maximum hmF2 (e.g., Morgan & Ballard, 1978).…”
Section: Large Scale Tid Detection Methodologiessupporting
confidence: 94%
“…The accuracy of ground-based single-site-location (SSL) HF radio wave direction finding is severely compromised by the passage of TIDs through the ionospheric reflection area (Nickisch et al, 2016). Small amplitude TIDs, occurring virtually all the time with varying amplitudes, similar to cloud occurrence in the troposphere, can tilt the reflecting isodensity contours by as much as 3°-5°.…”
Section: Introductionmentioning
confidence: 99%
“…This type of model has been implemented to model TIDs in several recent studies (Cervera & Harris, 2014;Mitchell et al, 2017;Nickisch et al, 2016), and the model itself was tested by Morgan and Calderón (1978) who found relatively good agreement with measurements. The main drawbacks of this model is that there is no viscosity effect to damp out the wave at higher altitudes, and that the scale height is constant with altitude.…”
Section: Tid Modelmentioning
confidence: 99%
“…In the present work, the effect of medium-scale TIDs (MSTIDs) on some characteristics of HF ray paths is analyzed. MSTIDs are often associated with the action of atmospheric gravity waves (GWs) [3,4], with periods ranging from several minutes to less than one hour and velocities from ~ 50 to 300 m s −1 . TIDs effect on ray paths can result in Doppler shift of the received signal and changes of the ray trajectories, which in turn can produce apparent fluctuations on return echoes from target in radar applications, and cause coordinate registration errors for over-the-horizon radars OTHR [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, ray path modifications by a simulated TID are obtained using a 3-D ray tracing algorithm developed by Jones and Stephenson [7], which was modified to include the 2016 version of the International Reference Ionosphere (IRI-2016) model [8], the US Naval Research Laboratory Mass Spectrometer and Incoherent Scatter radar model (NRLMSISE-00) [9], a realistic Earth's magnetic field using the International Geomagnetic Reference Field 12th generation (IGRF-12) model [10], and Hooke's TID model [11]. In addition to the links to these models, a cubic interpolation method was implemented to guarantee continuous first derivatives in the electron density profiles [4]. A set of simulations are analyzed to demonstrate the robust performance of this ray tracing technique.…”
Section: Introductionmentioning
confidence: 99%